A Rare Case Report of Localized Bullous Fixed Drug Eruption Due to Tamsulosin - Sheba Mariam Jacob; Thillaikarasi A; Narasimhalu C.R.V; Vimal Chander R (Dr. Annil Mahajan, 2023)
Fixed drug eruption is a cutaneous adverse reaction to a specific drug. Tamsulosin is an alpha-1 adrenergic receptor blocker used to treat benign prostatic hyperplasia in men. We report a case of 55-year-old man with benign prostatic hyperplasia who came with bullous eruption on the fingers of his left hand after 3 weeks of using Tab Tamsulosin 0.4 mg once daily at night. Two cases of fixed drug eruption due to Tamsulosin have been reported in literature before and therefore cutaneous adverse effect of tamsulosin should be kept in mind while prescribing the drug.